2017
DOI: 10.3168/jds.2016-11444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gradual or abrupt cessation of milking at dry off on milk yield and somatic cell score in the subsequent lactation

Abstract: The objective of this study was to assess the effect of milk cessation method (abrupt or gradual) at dry off on milk yield and somatic cell score (SCS) up to 120 d in milk during the subsequent lactation. Data from 428 cows from 8 dairy herds in Ohio were analyzed. Abrupt cessation cows kept the farm's regular milking schedule (2 or 3 times) through dry off and gradual cessation cows were milked once daily for the final week of lactation. Milk yield and SCS were collected using Dairy Herd Improvement Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
(48 reference statements)
2
12
0
2
Order By: Relevance
“…Yield refers to milk, fat, or protein yield, as will be clear from the context. Yield in the subsequent lactation depends on performance in the current lactation, such as gestation length (Foote, 1981;Mur-Novales et al, 2018), lactational milk yield (e.g., Kuhn et al, 2005a;Pinedo et al, 2011;Cermakova et al, 2014), SCC at dry-off (Gott et al, 2017), milk yield at dry-off (Bach and Pont, 2017), and DIM at dry-off (Gill and Allaire, 1976;O'Connor and Oltenacu, 1988;Weber et al, 2015). Results from field studies could be vulnerable to influences by unpredictable confounding factors.…”
Section: Data Description and Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield refers to milk, fat, or protein yield, as will be clear from the context. Yield in the subsequent lactation depends on performance in the current lactation, such as gestation length (Foote, 1981;Mur-Novales et al, 2018), lactational milk yield (e.g., Kuhn et al, 2005a;Pinedo et al, 2011;Cermakova et al, 2014), SCC at dry-off (Gott et al, 2017), milk yield at dry-off (Bach and Pont, 2017), and DIM at dry-off (Gill and Allaire, 1976;O'Connor and Oltenacu, 1988;Weber et al, 2015). Results from field studies could be vulnerable to influences by unpredictable confounding factors.…”
Section: Data Description and Editingmentioning
confidence: 99%
“…Drying off high-yielding cows introduces unnecessary stress (Friggens et al, 2004). The risk of mastitis may also increase when high-yielding cows are dried off (Enevoldsen and Sørensen, 1992;Gott et al, 2017) due to increased udder pressure (Bertulat et al, 2013). Zhao et al (2019) also offer other physiological mechanisms triggered by cessation of milk production, which suggest that high-producing cows may need a longer dry period for a complete renewal of their mammary gland.…”
Section: Effects Of Dry Period Length On Yields In the Subsequent Lactationmentioning
confidence: 99%
“…The 2 drying-off methods assessed were abrupt and gradual cessation of milking. The sample size for the larger project was calculated based on expected differences in udder health parameters between the treatment groups (Gott et al, 2017). The study reported here was conducted in a single large Holstein herd, which was enrolled in the larger study.…”
Section: Study Populationmentioning
confidence: 99%
“…In Chapter 5 and 6, in order to reduce milk yield in the week before drying off, cows were fed a dry cow ration from 7 days before the drying off day and were gradually ceased through milking once daily from 4 days before the drying off day till drying off. In previous studies, gradual cessation of milk before drying off decreased or did not affect IMI across the DP or SCC in the subsequent lactation (Gott et al;Newman et al, 2010). Compared with a lactation ration, feeding a dry hay ration before drying off was associated with a lower prolactin concentration, which facilitate drying off, but also with a lower plasma glucose, and greater FFA and BHBA concentration (Ollier et al, 2014).…”
Section: Milk Yield In Previous Late Lactation Associated With Postpartum Udder Healthmentioning
confidence: 77%